Investment under uncertainty, coalition spillovers and market evolution in a game theoretic perspective - Thijssen Jacco (Boston Kluwer Academic, 2004)
In this book, new models and techniques are developed to analyse economic dynamics in an uncertain environment. In the first part, investment decisions of firms are analysed in a framework where imperfect information regarding the investment's profitabil
Keywords: Applied statistics; Economics; Game theory